Implementation of Microsoft OneDrive Media Application in Social Studies Learning in High School - Hikmah Khoirunnisa; Nida Siyadati Albi; Wahyunengsih Wahyunengsih (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Asessing how well digital platforms work to improve student achievement is becoming increasingly important as these technologies become more widely adopted in the education sector. This study examines the contribution of Microsoft OneDrive in social studies learning at the secondary school level, with an emphasis on its potential to support learning flexibility, strengthen collaboration between students, and encourage learning autonomy. The lack of studies that specifically review the benefits of OneDrive in the context of the Indonesian education system, especially in the implementation of the Merdeka Curriculum, is a significant problem identified in this study. A descriptive, qualitative study employed the technique of document analysis on several instructional resources that utilize OneDrive. The results show that OneDrive facilitates the distribution of assignments, increases the accessibility of educational resources, enables immediate feedback, and encourages both solo and group learning methods. OneDrive also facilitates the synchronization of online learning methods with curriculum objectives. However, obstacles still exist, such as the lack of supporting facilities and educators' low digital skills. Overall, OneDrive is considered an instrumental tool in transforming social studies learning to a more responsive, efficient and student-oriented digital structure.